PALARIS palm-based recognition and identification system - Azurin, Amanda Jayne L. (1999)
There are many recognition systems that abound that are mainly based on the biometric and morphological features of an individual. Examples of which are fingerprint, face, voice and DNA identification techniques. In this paper, we present a plausible alternative basis for identity verification using the flexions and palmar ridges of the hand. The algorithm that was incorporated for was based on fingerprint minutiae detection and matching technique. Minutiae can be categorized on the basis of the number and location of the terminations and bifurcations of the ridgelines found on the palm. Ridges were extracted directly from gray-scale images as opposed to other methods that use pre-processing techniques such as edge enhancement, binarization, thinning and filtering. There were a great number of complexities that were encountered due to noisy and inept scanned images. But the difficulty was reduced by directly working on the original gray-scale image. The results that were accumulated were based on the type, location and angle displacement of each minutia. A statistical probability would be presented that is a measure of confidence of the matching process.